2022
DOI: 10.3390/agriculture12101703
|View full text |Cite
|
Sign up to set email alerts
|

Research on Environmental Governance, Local Government Competition, and Agricultural Carbon Emissions under the Goal of Carbon Peak

Abstract: By introducing network game theory, this paper analyzes the internal relationship and interaction mechanism among environmental governance, local government competition, and agricultural carbon peak level. On the basis of theoretical analysis, a spatial panel model is constructed using panel data from 30 provincial-level regions in China for empirical analysis. The research finds that local governments have positive competition with respect to the agricultural carbon peak, they adopt complementary carbon peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Generally, the relationship between ACEs and agricultural economic growth shows a bidirectional causality in both the short-run and the long-run [15]. It was found that the proportion of the rural population is negatively correlated with ACEs [16], and the decline in the level of rural human capital exacerbates ACEs [17]. Finance, such as rural inclusive finance, digital finance, and green finance, can all affect agricultural activities through some intermediate mechanisms, thus affecting ACEs [18,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, the relationship between ACEs and agricultural economic growth shows a bidirectional causality in both the short-run and the long-run [15]. It was found that the proportion of the rural population is negatively correlated with ACEs [16], and the decline in the level of rural human capital exacerbates ACEs [17]. Finance, such as rural inclusive finance, digital finance, and green finance, can all affect agricultural activities through some intermediate mechanisms, thus affecting ACEs [18,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are also lots of related works. Yang et al [25] found significant positive spatial spillover effect in the carbon emissions, and therefore, they believed that local environmental governance is more important. He et al [26] also concentrated on the spatial spillover effect and found evidence that local governments with a low level of economic development tend to follow the carbon emission reduction policies provided by the highly developed surrounding regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, it is not conducive to the promotion of industrial transformation and upgrading. Another view is the dynamic level of "innovation compensation" [45,46]. As the degree of environmental decentralization increases, strict environmental regulations imposed by the government will increase the production costs of enterprises.…”
Section: Theoretical Mechanism Analysis and Research Hypothesismentioning
confidence: 99%